Міжнародні чинники створення та діяльності інститутів політичного транзиту - Гаджиєва, Ділара Вагіфівна; Гаджиева, Дилара Вагифовна; Gadzhyieva, Dilara V. (My University, 2014)
Дисертація на здобуття наукового ступеня кандидата політичних наук за спеціальністю 23.00.04 – політичні проблеми міжнародних систем та глобального розвитку. – Національний університет «Одеська юридична академія», Одеса, 2014. У дисертації здійснено комплексне дослідження інститутів політичного транзиту, міжнародних чинників їх створення та діяльності та перспектив функціонування. Проаналізовано природу та теоретичний зміст поняття «політичний транзит», обґрунтовано формування концепції інститутів політичного транзиту в сучасній політичній науці. Вироблено визначення поняття «інститут політичного транзиту», встановлено та розкрито його функції та ознаки. Доведено, що інститути політичного транзиту є неодмінними супутниками політичних транзитів в глобалізованому суспільстві. Здійснено оцінку перспектив інститутів політичного транзиту в сучасному глобалізованому світі, де досвід демократизації переноситься з однієї країни до іншої. Встановлено, що основними тенденціями прояву міжнародно-політичного впливу на створення інститутів політичного транзиту є створення місій спостерігачів в перехідній країні, ініціація заходів внутрішньодержавного порозуміння, вироблення кроків щодо стабілізації економіки.

Диссертация на соискание ученой степени кандидата политических наук по специальности 23.00.04 – политические проблемы международных систем и глобального развития. – Национальный университет «Одесская юридическая академия», Одесса, 2014. В диссертации осуществлено комплексное исследование институтов политического транзита, международных факторов их создания и деятельности и перспектив функционирования. Проанализированы природа и теоретическое содержание понятия «политический транзит», обосновано формирование концепции институтов политического транзита в современной политической науке. Определено понятие «институт политического транзита», установлены и раскрыты его функции и признаки. Доказано, что институты политического транзита являются непременными спутниками политических транзитов в глобализованом обществе. Осуществлена оценка перспектив институтов политического транзита в современном глобализованом мире, где практика демократизации переносится из одной страны в другую. Установлено, что основными тенденциями проявления международно-политического влияния на создание институтов политического транзита являются создание миссий наблюдателей в переходной стране, инициация мероприятий внутригосударственного согласия, выработка шагов по стабилизации экономики.

Dissertation for the degree of Master of Political Sciences, specialty 23.00.04 – political problems of international systems and global development. – National University «Odessa Law Academy», Odessa, 2014. The dissertation is a complex research of institutions of political transition and international factors of their creation, activity and prospects of functioning. The nature and the content of the theoretical concept of “political transition” is analyzed. Considered that political transition is not linear process, and can have multi-vector nature. Political transition can cover all types of transition states of socio-political systems in terms of substantial change their character not only from authoritarianism to democracy, but on the contrary, according to national, cultural and political characteristics of the system. The definition of “institution of political transition” is given; its functions and features are described. Determined that the question of political institutions that actually take on the function of organization and practical implementation of political transition and, in fact, become the transitional institution remains open to political science. However, analysis of world history and contemporary practice of transformational changes confirms the fact that such conversion could not take place indirectly, in isolation from the institutional machinery of the state. This gap between political theory and political practice proves a real need for an introduction to the scientific terminology the category of the institution of political transition, and its detailed and comprehensive study. It is proved that the institutions of political transition are indispensable companions of transformation processes on the way to a renewed political and social system. The basic conceptual constructs in research of institutions of political transition, such as “provisional government” and “constituent assembly” are defined. Determined that constituent assembly is temporary, representative, parliamentary institutions authorized to issue new public-political system, to develop fundamental laws of a state and its constitution. Determined that provisional governments known in state practice as an institution of the executive branch, established as a result of the political crisis of the previous official government or when it was overthrown by an uprising or revolution. Methodological approaches for research of transitional phenomena are given. Special attention is paid to synergetic approach as a perspective methodology for studying political transitions through the prism of the bifurcation theory. Systems approach studied system properties of political transition, its interaction with other elements of the system, including the institution of political transition as its integral component. The necessity of applying of the comparative method to the study of international experience of political transitions and their comparison in order to highlight the positive and negative features is given. The urgency of the application of historical method with its possibility to identify patterns and contradictions in the development of researched subject is lined. The necessity of the application of institutional method and the principle of institutional complexity for the study of the patterns of institutional development in transitive countries is emphasized. Established that international political influence on political processes in the country is channeled towards the creation of institutions political transition as the only legitimate institution during transitive changes, resulting in a desire to interact only with its institution and recognize the power that was installed as a result of its constitutive work. The impact of the international community can take place through authoritative governmental and non-governmental international organizations, missions, forums, transborder cooperation. The main trends of international political impact on the creation of institutions of political transition are the observer missions in transition countries, the initiation of activities for domestic harmony, developing of steps for economic stabilization. It was concluded that since democracy is closely intertwined with other global and civilizational processes, especially with globalization, which makes continuous growth of interdependence among countries in the future globalized world trend to increased international political influence only intensify, including in connection with the deepening of integration between countries. By this, greater use of institutions of political transition in transitional processes called up to harmonize and improve the current political process.
Гаджиєва Д. В. Міжнародні чинники створення та діяльності інститутів політичного транзиту : автореф. дис. ... канд. політ. наук : 23.00.04 / Д. В. Гаджиєва; кер. роботи М. А. Польовий; Нац. ун.-т "Одеська юридична академія". – Одеса, 2014. – 19 с.
Keywords: політичний транзит; політичні інститути; міжнародні чинники; світова спільнота; міжнародно-політичний вплив; глобалізація; глобальна демократизація; политический транзит; политические институты; международные факторы; мировое сообщество; международно- политическое влияние; глобализация; глобальная демократизация; political transition; political institutions; international factors; world community; international political impact; globalization; global democratization